Femoral Pathological Fracture as the First Clinical Manifestation of Papillary Thyroid Carcinoma in a Primigravida. (4th April 2013) - Abu-Zaid, Ahmed; Azzam, Ayman; Al-Hindi, Hindi; Amin, Tarek
Abstract : Papillary thyroid carcinoma is the most common differentiated type of thyroid malignancy. It is largely a loco-regional disease with a high tendency to metastasize to regional cervical lymph nodes. Distant hematogenous metastases are very rare and primarily include lungs and bones. Distant bone metastases are present in approximately 1.7% of patients with differentiated thyroid malignancy. Sternum, ribs, and spine are the most frequent sites of osseous metastases. Up to our knowledge, we report the first occurrence of an extra nodal metastasis of papillary thyroid carcinoma to a femoral bone presenting as a pathological fracture in a 21-year-old 37-week primigravida. We report this case because of its unusual site of metastasis and atypical presentation during pregnancy. Moreover, we briefly elaborate on the management of such uncommon cases.